PENDUGAAN POTENSI LESTARI KEMBUNG (Rastrelliger spp.) DI PELABUHAN PERIKANAN SAMUDERA BELAWAN SUMATERA UTARA (Potential Estimation on Sustainable of Mackerel Fish (Rastrelliger spp.) on Belawan Ocean Fishing Port North Sumatera) - Putri Permata Sari Sirait; Mohammad Basyuni; Desrita Desrita (Program Studi Manajemen Sumberdaya Perairan, Fakultas Pertanian Universitas Sumatera Utara, 2016)
Highly market demand on Mackerel fish (Rastrelliger spp.) effected overfishing without controling by fishermen. The purpose of this research was to determine the potential of sustainable with optimum effort, utilization rates and insistence, sustainability and management of fish resources in Malacca Strait. The analysis of data compresed catches data and fishing effort of Mackerel last 10 years from the Belawan Ocean Fishing Port North Sumatera. The potential of sustainable prediction was performed with Fox model. Value Maximum Sustainable Yield (MSY) Mackerel fish was 6,276,538.129 kg / year with optimum effort was 7939.647596 trips / year. Average utilization rate of 70,39% with an average insistence rate (TAC) 179,49%, while allowable catch 150,1587365 kg/year. Based on the value of MSY and optimum effort Mackerel fish has been overfishing. While based on average utilization rate, Mackerel fish in Belawan aquatic was still in condihtion of solid catch.Keywords : Malacca Strait, Potential, Rastrelliger spp., Sustainability, Utilization